Ministries of Education in small states: Case studies of organisation and management (Commonwealth Secretariat, 1991)
This book is a companion to another volume entitled "Making Small Practical: The Organisation and Management of Ministries of Education in Small States." It includes 14 country studies, which are arranged by region, with five on the Caribbean region
Keywords: Small states